DEVELOPING ENGLISH LEARNING MATERIALS SUPPLEMENTED BY E-LEARNING FOR THE TENTH GRADE NURSING DEPARTMENT STUDENTS OF SMK NEGERI 1 KUBUTAMBAHAN - ., Eva Agustino; ., Made Hery Santosa, S.Pd, M.Pd., Ph.D.; ., I Putu Ngurah Wage Myartawan, S.Pd., M.P (Jurnal Pendidikan Bahasa Inggris undiksha, 2017)
Penelitian ini merupakan penelitian dan pengembangan (R&D) yang bertujuan untuk (1) mengembangkan materi Bahasa Inggris yang dibutuhkan oleh siswa kelas X Jurusan Keperawatan di SMK Negeri 1 Kubutambahan; (2) mengidentifikasi desain materi Bahasa Inggris; dan menentukan (3) kualitas materi Bahasa Inggris yang dikembangkan berdasarkan kriteria dari materi ESP yang baik dan kriteria e-learning yang baik. Penelitian ini dilakukan berdasarkan pada desain penelitian dan pengembangan oleh Lee & Owens (2004). Desain ini meliputi: need analysis, design dan development. Data dikumpulkan melalui observasi, rekaman, interview, dan uji ahli. Data yang didapatkan dari hasil observasi, rekaman dan interview selama proses need analysis, telah dianalisis secara deskriptif, sedangkan data yang didapatkan dari hasil uji ahli, dianalisis secara kuantitatif dengan mengikuti rumus dari Candiasa (2010). Hasil dari penelitian menunjukkan bahwa; (1) siswa kelas X Jurusan Keperawatan membutuhkan materi Bahasa Inggris yang spesifik sesuai dengan target pekerjaan yang mereka lakukan di masa depan; (2) materi Bahasa Inggris telah didesain menjadi beberapa unit, yaitu: General Assessment, Handling Patients, Patient’s Hygiene, Checking Vital Signs, dan Dimensions of Symptom; (3) dari hasil uji ahli yang berdasarkan dengan kriteria materi ESP yang baik dan kriteria e-learning yang baik, materi yang dikembangkan tergolong sangat bagus. Kata Kunci : need analysis, e-learning, materi bahasa inggris, R&D This study was a research and development (R&D) was aimed at (1) developing English learning material that are needed by the tenth grade of Nursing Department students at SMK Negeri 1 Kubutambahan; (2) describing the design of English learning material; and finding out (3) the quality of the developed material based on the criteria of good ESP material and good e-learning. This study followed the R&D design by Lee and Owens. This design involves: need analysis, design, and development. This study was conducted at SMK Negeri 1 Kubutambahan, the subjects of the study being the tenth grade of Nursing Department students. The data were collected through observation, recording, interview, and expert judgment. The data from the result of observation, interview and recording during the need analysis process were analyzed descriptively; the data from expert judge were analyzed quantitatively. The result of this study shows that: (1) the tenth grade of Nursing Department students need specific English materials that are related to their future job. The existing syllabus and material did not cover their needs; (2) the materials were designed into some unit based on the data gathered from the need analysis. Those units are: General Assessment, Handling Patients, Patient’s Hygiene, Checking Vital Signs, and Dimensions of Symptom; (3) from the result of the expert judgment based on the criteria of good ESP material and good e-learning material, the developed material was categorized into an excellent material.keyword : need analysis, e-learning, English learning material, R&D